Placenta accreta - Nizami, DJ; Awasthi, RT; Dash, S; Verghese, J (Kathmandu University Medical Journal, 2010)
Total placenta accreta is a rare condition. Its management is a dilemma. Attempted separation of the placenta in placenta accreta can cause torrential blood loss. Therefore an antenatal diagnosis of placenta accreta permits advance planning of delivery. Two alternatives are caesarean section through the fundus with subsequent immediate hysterectomy, which has traditionally been the treatment of choice or if the patient wishes more children, leaving the placenta in place and managing conservatively1. We present a 38 year old lady who was diagnosed to have placenta accreta while performing a caesarean section for a breech presentation. We had to proceed with a total hysterectomy. DOI: 10.3126/kumj.v7i2.2710 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 149-151